Clinical, biochemical and haematological changes in leptospirosis - Modi, Rahul A.; Patel, Ankita K.; Patel, Mubin I.; Padsala, Suresh G. (International Journal of Research in Medical Sciences, 2018)
Background: Leptospirosis is a globally important zoonotic disease caused by pathogenic leptospira. Leptospira species are spirochetes belonging to the order spirochetes and the family leptospiraceae. Present study is done to find out the incidence of thrombocytopenia in leptospirosis and to correlate it with other parameters like renal dysfunction, hepatic dysfunction and bleeding manifestation. Methods: Study includes 51 clinically suspected and diagnosed cases of leptospirosis, in Government hospital, South Gujarat, during a period from January 2017 to December 2017. Clinical signs and symptoms and complications, biochemical profile like bilirubin and creatinine, haematological profile like Hb, WBC count and platelet count were recorded. Thrombocytopenia was defined as a platelet count below 1,50,000/cmm. Results: The present study includes 51 cases of Leptospirosis. Age ranged from 16 years to 61 years (male-39 and Females-12) There were 38 (74.5%) cases with thrombocytopenia and 13 (25.4%) cases with normal platelet count. Out of 38 thrombocytopenic cases, 32 (84.2%) cases had renal dysfunction, 26 (68.4%) cases had hepatic dysfunction and 16 (42.1%) cases had pulmonary haemorrhage. Among 13 cases with normal platelet count, 8 (61.5%) cases had hepatic dysfunction and 7 (53.8%) cases had renal dysfunction and 3 (23%) cases had pulmonary haemorrhage. Conclusions: Thrombocytopenia is a frequent complication (present in more than half of the patient) in leptospirosis and associated with more frequent and more severe complications. Therefore, early recognition of thrombocytopenia is recommended to prevent complications and mortality in leptospirosis.